Experience of domestic violence among the pregnant women. - Gurung, Saraj (2009)
ABSTRACT: The study entitled "Experience of Domestic Violence among the Pregnant Women" was carried out in Triyuga Municipality, Udayapur, Nepal. This was a qualitative study carried out in 18 pregnant women. The main objective of the study was to explore the experience of domestic violence among the pregnant women. A phenomenological approach was used and purposive and snowball sampling techniques were used. The data was gathered through in-depth interview, observation and Focus Group Discussion (FGD) with guidelines. In-depth interview were carried out with each participants along with audio tape recording and field notes. The facial expressions, gesture, tone of voice and emotions were observed among the participants during interview. A focus group discussion was conducted with 10 members of Community Based Organization (CBO) who are working towards the women's issues and against the domestic violence for triangulation. The study findings revealed that 11out 18 of the participant were multi gravid. Six participants had experienced emotional violence and 1 out of 6 the participant had experienced emotional and physical violence both in present pregnancy. The extent of violence were related to emotional violence during pregnancy perpetrated by husband, mother in-law, father in-law and sister in-law. The nature of emotional violence experienced were verbally abused, threatened to leave spousal house, threatened for remarriage, accused as witch craft, blamed for induced abortion, they were not allowed to seek health care when needed and restricted to enter the kitchen and their belongings were thrown out etc. The physical violence experienced by the participants were punched, pushed on the floor/walls, slapped, kicked, beaten every where in the body, hit by fire wood and hair was pulled. One participant had experienced emotional violence and another one had experienced physical and emotional violence in previous pregnancy. The causes behind it were inter caste marriage, sub fertility, not working properly at home, dowry related and personal habits of alcoholism/ gambling of the husband etc. The consequences of domestic violence exhibited by the pregnant women felt pain and agony, feeling helpless, wanted to terminate the present pregnancy, wanted to break the marital relationship, feeling to suicide, backache, and high blood pressure. The participants responded the violence in terms of keeping silence, crying, making busy in household chores and sharing with the members of women group in own village. The study also revealed that they seek help for community mediation from women's group and one participant has filed the case to the police office after failure of community mediation. The participants were unaware about the existing legal system. During the process of triangulation it has been found that, local CBO members view was similar to the study participants. They expressed the nature of domestic violence has changed into physical to emotional and reporting of the incidence is increasing. The reason behind it was gender based socio-cultural and economic discriminatory practices. They emphasized that domestic violence should be controlled by the society/state with an amendment of Act and Laws against it and strong implementation. They also stressed the women empowerment plays an important role against domestic violence. To conclude, it is recommended that similar type of study to be conducted by using both quantitative and qualitative approach to make the findings more valid.